Metabolism and mechanism of action of 5-fluorodeoxycytidine. - Newman, E M (1982)
5-Fluoro-2'-deoxycytidine (FdCyd) is a potent inhibitor of growth of tissue culture cells. The major cytotoxic event appears to be inhibition of thymidylate synthetase as evidenced by reversal of the cytotoxicity with thymidine but not deoxycytidine and by the effect of FdCyd on nucleotide pools, which is characteristic of specific inhibition of this enzyme. The metabolism of FdCyd was established by using a method in which its cytotoxicity was compared in several S-49 mutant cell lines having defined single or double deficiencies of enzymes involved in nucleoside and nucleotide metabolism. Our results indicate that FdCyd is metabolized to 5-fluoro-2'-deoxyuridylate, a potent inhibitor of thymidylate synthetase by two pathways: (i) sequential reactions catalyzed by deoxycytidine kinase and deoxycytidylate deaminase and (ii) sequential reactions catalyzed by cytidine deaminase and thymidine kinase. We have shown that metabolism of FdCyd can be directed through the former pathway by inhibition of cytidine deaminase with tetrahydrouridine. Since cytidine deaminase appears to be responsible for catabolism of FdCyd in animals, our results suggest that the antineoplastic effects of FdCyd should be examined in combination with inhibitors of cytidine deaminase.